Techno-economic study of gas turbines with hydrogen, ammonia, and their mixture fuels - Amir Mohammad Yazdani; Mohsen Salimi; Majid Amidpour (Heliyon)
Ammonia is a versatile energy carrier without carbon emissions that can be used for power generation. In this article, a techno-economic analysis has been done to predict the levelized cost of electricity production using gas turbines with clean fuel in Iran. In the technical discussion, the analysis of different scenarios of ammonia and hydrogen fuel composition ratio was done, and by keeping the turbine inlet temperature to the same gas turbine as the SGT5-2000E turbine, the output power in different fuel ratios is around 192.8–229.0 MW was variable and reached the maximum value in some proportions. Also, in the economic discussion, the effects of fuel cost and interest rate parameters were investigated, sensitivity analysis was performed on different combined ratios of ammonia and hydrogen in fuel, and an economic analysis of the ideal ratio was conducted. The price of ammonia fuel was calculated from 222 $/ton to 2000 $/ton, and the levelized cost of electricity production changed from 91.7 $/MWh to 673.4 $/MWh. Additionally, an economic comparison was made between the utilization of ammonia-hydrogen and natural gas fuels. This alternative fuel can be a promising way to produce power without carbon emissions and suitable storage for renewables.